Matematyka

Autorzy:Jerzy Janowicz

Wydawnictwo:Nowa Era

Rok wydania:2015

Oblicz wartość wyrażenia, korzystając z własności ... 4.6 gwiazdek na podstawie 5 opinii
  1. Gimnazjum
  2. 1 Klasa
  3. Matematyka

`a) \ sqrt{9^2*9^3}:sqrt{9^4}=sqrt{9^(2+3)}:sqrt{9^4}=sqrt{9^5}:sqrt{9^4}=` 

`\ \ \ =sqrt{9^5:9^4}=sqrt{9^(5-4)}=sqrt{9}=3` 

   


`b) \ [(sqrt{49})^6:(sqrt{49})^5]*[(sqrt{49})^2:sqrt{49}]=` 

`\ \ \ =(sqrt{49})^(6-5)*(sqrt{49})^(2-1)=sqrt{49}*sqrt{49}=` 

`\ \ \ =sqrt{49*49}=sqrt{49^2}=49`